The role of grid extensions in a cost-efficient transformation of the European electricity system until 2050 - Michaela Fürsch; Simeon Hagspiel; Cosima Jägemann; Stephan Nagl; Dietmar Lindenberger; Eckehard Tröster (Institute of Energy Economics at the University of Cologne (EWI), 2012)
As an attempt to fi ght global warming, many countries try to reduce CO2 emissions in the power sector by significantly increasing the proportion of renewable energies (RES-E). A highly intermeshed electricity transmission grid allows the achievement of this target cost-efficiently by enabling the usage of most favorable RES-E sites and by facilitating the integration of fluctuating RES-E infeed and regional electricity demands. However, construction of new lines is often proceeding very slowly in areas with a high population density. In this paper, we try to quantify the bene ts of optimal transmission grid extensions for Europe until 2050 compared to moderate extensions when ambitious RES-E and CO2 reduction targets are achieved. We iterate a large-scale dynamic investment and dispatch optimization model for Europe with a load-flow based transmission grid model, in order to determine the optimal deployment of electricity generation technologies and transmission grid extensions from a system integrated point of view. Main findings of our analysis include that large transmission grid extensions are needed to achieve the European targets cost-efficiently. When the electricity network is cost-optimally extended, 228,000 km are built until 2050, representing an increase of 76% compared to today. Further findings include substantial increases of average system costs for electricity until 2050, even if RES-E are deployed efficiently throughout Europe, the grid is extended optimally, and if signi cant cost reductions of RES-E are assumed.
Keywords: C61; C63; Q40; Q58; 330; Renewable energy; GHG reduction; transmission grid; power system optimization